Use of Protein Kinase–Focused Compound Libraries for the Discovery of New Inositol Phosphate Kinase Inhibitors. (October 2018) - Puhl-Rubio, Ana C.; Stashko, Michael A.; Wang, Huanchen; Hardy, P. Brian; Tyagi, Vikas; Li, Bing; Wang, Xiaodong; Kireev, Dmitri; Jessen, Henning J.; Frye, Stephen V.; Shears, Stephen B.; Pearce, Kenneth H.
Inositol hexakisphosphate kinases (IP6Ks) regulate a myriad of cellular processes, not only through their catalytic activity (which synthesizes InsP7, a multifunctional inositol pyrophosphate signaling molecule) but also through protein–protein interactions. To further study the enzymatic function and distinguish between these different mechanisms, specific inhibitors that target IP6K catalytic activity are required. Only one IP6K inhibitor is commonly used: N 2-( m -(trifluoromethyl)benzyl) N 6-( p -nitrobenzyl)purine (TNP). TNP is, however, compromised by weak potency, inability to distinguish between IP6K isoenzymes, off-target activities, and poor pharmacokinetic properties. Herein, we describe a new inhibitor discovery strategy, based on the high degree of structural conservation of the nucleotide-binding sites of IP6Ks and protein kinases; we screened for novel IP6K2 inhibitors using a focused set of compounds with features known, or computationally predicted, to target nucleotide binding by protein kinases. We developed a time-resolved fluorescence resonance energy transfer (TR-FRET) assay of adenosine diphosphate (ADP) formation from adenosine triphosphate (ATP). Novel hit compounds for IP6K2 were identified and validated with dose–response curves and an orthogonal assay. None of these inhibitors affected another inositol pyrophosphate kinase, PPIP5K. Our screening strategy offers multiple IP6K2 inhibitors for future development and optimization. This approach will be applicable to inhibitor discovery campaigns for other inositol phosphate kinases.